SCIENTIFIC WRITING SYSTEM OF ORDERING GOODS AT PT. DIAMOND BEST - Zahir Fadli; Sunarto Usna Drs. MMSI (Jurnal Sistem Informasi, 2003)
The high quantity of daily transactions has also increased the time needed to performthe process of ordering products, so the accuracy and efficiency of time getting theinformation desired is not achieved as desired. To overcome this, the writer makes thedesign system, ordering of goods to resolve the issue. By designing the system,ordering of goods it is expected that the problems faced in ordering goods can besolved.With the goods enter the data item and store data as well as ordering goodstransaction into the computer via a customized menu with the transaction process, theease - the ease which was made on this system is more biased in time and costefficiency, good accuracy in the process of calculation, calculation of goods data andother bias is reached.